SOCIAL PROJECTS AS A TOOL OF INNOVATIVE SOCIAL POLICY: INTERNATIONAL EXPERIENCE AND NATIONAL CONTEXT (INNOVATIVE ECONOMY, 2025)
Shynkaruk L.V., Prushkivska E.V., Bondarenko L.A.  SOCIAL PROJECTS AS A TOOL OF INNOVATIVE SOCIAL POLICY: INTERNATIONAL EXPERIENCE AND NATIONAL CONTEXTPurpose. The aim of the article is to determine the role of social projects as a tool for innovative social policy based on an analysis of international experience and to outline the possibilities for their adaptation to the Ukrainian context in the conditions of military and post-war transformations.Methodology of research. The research uses a systematic approach, structural-functional analysis and a comparative method to identify patterns in the development of social projects in different regions of the world (EU, USA, Asia, Latin America). Content analysis of regulatory and legal documents, strategic programmes of international organisations (EU, UNDP, OECD, World Bank) and national acts of Ukraine was used to assess the institutional environment for the implementation of social projects. The empirical basis consisted of statistical reports, analytical reviews and practices of implementing projects in the social sphere, which made it possible to determine their effectiveness and innovative potential. The generalisation of the results makes it possible to outline strategic approaches to the formation of social policy based on social projects and their effective integration into the national system.Findings. It has been established that social projects are a strategic tool for modernising social policy, ensuring the innovative nature of social change, institutional stability and investment in human capital. In EU countries, their implementation is based on a high level of institutionalisation and partnership with communities. In the United States, the emphasis is on the use of entrepreneurial tools, impact financing and systematic evaluation of the effectiveness of social projects. In Asian countries, models based on the integration of digital solutions and community-based approaches that ensure the active participation of local communities play a leading role. In Latin America, social projects are mainly developed within the framework of poverty reduction and inclusive development programmes aimed at reducing structural inequality. For Ukraine, social projects are of critical importance in the context of war and post-war reconstruction, as they provide support to vulnerable groups, develop social infrastructure, reintegrate veterans, stimulate entrepreneurship and attract international resources. The analysis identified three fundamental functions of social projects in contemporary development strategies, covering the investment dimension, which involves the mobilisation of financial and institutional resources; the innovation dimension, which shapes new models of social interaction; and the institutional and stabilisation dimension, which strengthens the capacity of communities and state institutions. A synthesis of these provisions gives grounds to assert that social projects should form the conceptual basis for shaping Ukraine's innovative social policy and determine its strategic guidelines in the context of transformational challenges.Originality. The scientific novelty lies in the comprehensive integration of international and national experience of social projects within a single conceptual model that includes institutional, innovative and investment dimensions. Unlike previous studies, the proposed interpretation considers social projects not only as socially oriented measures, but as a mechanism for the systemic transformation of social policy and the formation of a new institutional environment. A typology of international regional models has been created and the prospects for their adaptation to Ukraine have been identified, taking into account military risks, demographic changes and the needs of post-war reconstruction.Practical value. The results obtained can be used by state authorities and local self-government bodies to develop social programmes and projects aimed at supporting human capital and strengthening social inclusion. Social projects are a tool for shaping innovative social policy and modernising social services in the context of post-war reconstruction. The proposed approaches create the basis for a project-oriented model of social policy with the integration of innovation, partnership and sustainable socio-economic impact.Key words: social projects, social policy, investment, innovation, institutional environment, international experience, countries of the world, inclusion, employment, human capital, post-war reconstruction.
Keywords: social projects; social policy; investment; innovation; institutional environment; international experience; countries of the world; inclusion; employment; human capital; post-war reconstruction